Digital Resources in History Teaching with Reference to the European Project Europeana - Marsenić, Miloš; Stanojević, Saša (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The development of new technologies and the information society has accelerated changes in everyday life and modern teaching. Information and communication technologies (ICT) better motivate students to learn. In order to better preserve historical sources, they are digitized and thus protected, hence researchers can access the source faster and at a less cost. The possibilities of using the Internet in teaching are vast. It is necessary for schools to have computers, as well as for teachers and students to be motivated to use new electronic sources. Many websites have original historical material, from written and printed sources to audio-visual ones. We can call all this material digital resources (materials, sources, electronic historical sources). Teachers need to create engaging and imaginative teaching materials. However, a critical approach and caution in working with materials from the internet is essential. It is the teacher’s responsibility to recommend verified sites and documents. Much of the material on the Internet has been posted with the conscious intention of spreading inaccurate data. The possibilities of ICT are great in history studies, as well. It is possible to modernize teaching at all levels of studies, but the financial capabilities of schools do not allow the possibility of keeping up with those innovations. One of the web portals that can be used for teaching purposes with its digitized content is Europeana. It is a database of the cultural and historical heritage of Europe, through which it is possible to search the digitized material of institutions. The Europeana portal is a broad project that provides free access to tens of millions of digital units. One of the most important collections within this portal is dedicated to the First World War and is called Europeana 1914–1918.